Heterosexuality and Race in the Australian Same-Sex Marriage Postal Survey. Issue 97 (3rd July 2018) - Hegarty, Benjamin; Marshall, Daniel; Rasmussen, Mary Lou; Aggleton, Peter; Cover, Rob
ABSTRACT: This article argues that race and class are central aspects of sexual citizenship in a Australia. It does so by investigating representations of heterosexuality that were produced and circulated during the 2017 same-sex marriage postal survey. Engaging with feminist and critical race theorists, we position same-sex marriage as not exceptional but part of a wider distribution of sexual citizenship within Australia's ongoing settler colonial history. We do so by introducing a number of illustrative examples of representations of heterosexuality produced during the survey. These representations reveal how same-sex marriage perpetuated heterosexual authority by asserting claims to authenticity and the occupation of space. We observe how heterosexuality in the survey material reproduced fantasies linking these three themes, for example, in an authentic white heterosexual family who speaks from their suburban backyard. It reveals that ceding to a bifurcated view of either progressive or conservative voices forestalls rather than advances other visions which may exceed the limited imaginings of sexual citizenship offered by the white liberal settler colonial state.